Analisis Historiografi Orientalis: Sejarah Islam dan Nabi Muhammad dalam Islam: A Historical Survey Karya Hamilton Alexander Rosskeen Gibb - Kurniawati, Ravita Laelatul (Historia Madania: Jurnal Ilmu Sejarah, 2025)
Orientalists often have different views from Muslim historians regarding the history of Islam and the Prophet Muhammad. So this research examines the history of Islam and the Prophet Muhammad from the perspective of H.A.R. Gibb who is an orientalist. This research focuses on Gibb's perspective on early Islamic history and the Prophet Muhammad in his work entitled Islam a Historical Survey. The purpose of this research is to see how the emergence and development of Islamic historiography written by orientalists, and describe the history of Islam and the Prophet Muhammad written by Gibb. This research is a qualitative research whose explanation is based on analysis. The result of this research is that the emergence of modern philosophies in the form of humanism, secularism, and positivism influenced the development of western thought so that more and more orientalists studied Islam. The development of orientalist historiography is in line with the development of orientalism itself which is divided into four phases. Gibb's perspective on the history of Islam is that Islam in the early days had political and economic motives, and Gibb views that Islam can spread in various regions not because of its teachings, but the morals of the Prophet Muhammad as a preacher. Gibb's historiography uses new methods and new approaches in the form of social, cultural, and economic that can contribute to further Islamic historiography.Keywords: Historiography, Orientalist, H.AR. Gibb, Islamic History, Prophet Muhammad.